Effect of Cutting Speed on Surface Roughness in Stepped Turning of ST37 Mild Steel Using HSS Cutting Tools: A Six Sigma DMAIC Approach - Mhd Ardiansyah Damanik; Najwa Aprilia; Mabar Yoan A.S Gultom; Hasbi Shafwan Saragih; Fathir Salman (Inspire Global Insight Journal, 2026)
Surface roughness is a critical quality indicator in manufacturing processes, directly influencing the functional performance and service life of machined components. This experimental study investigates the effect of cutting speed on the arithmetic mean roughness (Ra) of ST37 mild steel workpieces subjected to conventional stepped turning using High-Speed Steel (HSS) right-hand cutting tools. A constant spindle speed of 325 rpm was applied while four stepped diameters — Ø19 mm, Ø20 mm, Ø22 mm, and Ø24 mm — were machined, yielding cutting speeds of 19.40, 20.42, 22.46, and 24.50 m/min, respectively. Surface roughness was measured at three axial positions per diameter using a contact-type surface roughness tester, and the arithmetic mean roughness (Ra) was recorded as the primary response variable. A Six Sigma Define–Measure–Analyze–Improve–Control (DMAIC) framework was applied to structure the quality analysis and identify improvement strategies. The results demonstrated that mean Ra values ranged from 2.234 µm (Ø20 mm) to 3.621 µm (Ø22 mm). The lowest roughness was attained at a cutting speed of 20.42 m/min, while the highest roughness was recorded at 22.46 m/min, revealing a non-linear relationship between cutting speed and surface quality. This non-monotonic behaviour is attributed to dynamic interactions among machine vibration, chip formation instability, and tool-workpiece contact conditions. The DMAIC analysis identified cutting speed optimisation within a 20–24 m/min range as the primary improvement lever. These findings provide practical guidance for selecting machining parameters that balance surface quality and productivity in stepped turning operations.